Use of Pele’s tears and spheres as an indicator of lava fountain height in Hawaiian volcanoes - Moyer, Scott; Sahagian, Dork (Frontiers in Earth Science, 2024)
Lava flows have presented the greatest hazard to human property during the most recent eruptions of Hawaiian volcanoes, and lava fountains are a source of these lava flows. The height of Hawaiian lava fountains reflects the exsolved gas content of the magma that controls eruption intensity. However, fountain height is not always observed, so we sought a proxy to estimate fountain heights of eruptions that were older or otherwise unobserved. Here, methods are described to empirically derive a relationship between the modal diameter of vesicles within Pele’s tears and spheres and lava fountain height, using samples of Pele’s tears produced during the last eruptions of Kīlauea Iki (1959) and Mauna Ulu (1969). The tears used to develop these relationships were approximately 1 to 4 mm in diameter. Additionally, since lava fountains 50–580 m high were used, the relationships we describe may only describe lava fountains in this height range. The strongest empirical relation follows the trendline Hmax = −2575d + 820, where Hmax is maximum lava fountain height and d is modal vesicle diameter. This empirical relationship may be applied to sub-Strombolian eruptions of tholeiite basalt that were not directly measured or observed to assess long-term shifts in lava fountain heights and thus the exsolved gas contents of a volcanic system. While the same conceptual framework can be applied beyond Hawai’i, the quantitative empirical relation may be slightly different in different systems, depending on total dissolved volatiles, magma chemistry and other factors.